Ethical AI Communication and Public Trust: Examining the Role of Transparency in Digital Media - Mohammad Nawab Turan; Musawer Hakimi; Hamayoon Ghafory; Ahmad Jamy Kohistani (COMMUSTY Journal of Communication Studies and Society, 2026)
The rise of Digital Media incorporating Artificial Intelligence raises important issues related to public trust; algorithmic transparency; and ethical standards for communication. In this study, a mixed methods approach was used to explore AI transparency disclosure practices and their association with public trust in digital media among a sample of 1,247 adults across six countries. The study utilized a survey instrument developed for this study, as well as qualitative thematic analysis of 614 open-ended responses. Results showed that disclosure of transparency practices accounted for the largest variation in public trust (beta = .38, p < .001). It also revealed moderating effects of digital media literacy and media skepticism on trust. A confirmatory structural equation model with a reasonable fit (CFI = .96, RMSEA = .048) provided validation of the Integrated Ethical AI Communication Framework. The study also indicated that structured transparency mechanisms; formalized oversight of editorial content; and explicit policies holding algorithms accountable to ensure transparency would substantially increase public trust across all demographic subgroups viewed to have access to digital news services. The findings indicate, in particular, that digital newsrooms should pair AI transparency disclosures with active media literacy initiatives, and that regulators should mandate minimum content standards for algorithmic disclosure rather than mere disclosure presence, in order to realise the full trust-building potential of ethical AI communication.